The Role of Sumba Women Weavers in Family Economic Empowerment: A Case Study of Ikat Weaving Preservation in Sumba, NTT - Tasya Widya Krisnadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study examines the role of Sumba women weavers in empowering the family economy through the preservation of the ikat weaving culture in East Nusa Tenggara (NTT). Using a qualitative approach, this study explores the socio-economic dynamics of weavers' families, women's strategies in managing the ikat weaving business, and its impact on family welfare. The results showed that weaving activities not only functioned as a means of cultural preservation but also became a significant alternative source of income for families. Women weavers play a dual role as custodians of cultural heritage and supporters of the family economy, often making weaving work a 'lifeline' when the family's economic conditions are unstable. However, they still face challenges such as limited access to capital, training, and wider markets. Identified empowerment efforts include improving business management skills, facilitating access to productive resources, and developing marketing networks. This research highlights the importance of integrated support from various stakeholders to optimize the potential of Sumba ikat weaving as an instrument of family economic empowerment while preserving valuable cultural heritage.